Geographical variation in anti-diabetic prescribing in Ireland in 2013 and 2014: a cross-sectional analysis. (2nd May 2017) - Murphy, Mark E; Bennett, Kathleen; Fahey, Tom; Smith, Susan M
Abstract: Background: Several new medications for type 2 diabetes (T2DM) have been introduced, including dipeptidyl peptidase-4 (DPP-4) inhibitors and glucagon-like peptide-1 receptor (GLP-1) agonists. Variation in the prescribing of these agents has implications for quality, safety and costs. We aimed to investigate geographical variation in the prescribing of anti-diabetic medications in Ireland. Methods: Cross-sectional analyses were undertaken on the two main national pharmacy claims databases in Ireland in 2013 and 2014. Direct standardized rates of individual anti-diabetic medication prescribing per 100 000 population were calculated by geographical area. Variation in prescribing was assessed using the systematic component of variation (SCV) and classified as very high (>10), high (5.4–10), moderate (3–5.4) or low (<3). Estimated total costs of prescribing were calculated per geographical area using medication wholesale costs. Results: Very high levels of geographical variation of GLP-1 agonists (SCV 11.4 and 10.3 in 2013 and 2014) and moderate variation of DPP-4 inhibitors (SCV 3.8 and 4.1) were found. There was low/moderate variation in the prescribing of sulphonylureas (SVC 2.8 and 3.6) and low variation in prescribing of metformin (SVC 1.7 and 2.0). Geographical variation in Ireland leads to an estimated total wholesale cost differential of €500 000 for GLP-1 agonists, per 100 000 population, between the highest and lowest prescribing areas. Conclusions: There is substantial geographical variation in the prescribing of new T2DM medicines, particularly GLP-1 agonists. The prescribing variation which was identified may not only represent differences in the application of clinical guidelines, but also variation in professional opinion or patient preference.